R&D policies for young SMEs: Input and output effects - Dirk Czarnitzki; Julie Delanote (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper evaluates the current focus of EU policy makers on small and medium-sized, young independent firms in high-tech sectors. Therefore, the effect of subsidies on both R&D input and R&D output is compared between independent high-tech young firms (NTBFs), independent low-tech young firms (LTBFs) and their non-independent counterparts. A treatment effects analysis reveals that full crowding-out with regard to public funding is rejected for all firm types. However, the treatment effect is highest for independent high-tech firms. The indirect effect of subsidies on R&D output is evaluated within a patent production framework. These results show that independent high-tech firms have no lower output effects than other firms and thus suggest that the current policy focus on certain firm types is not ineffective.
urn:nbn:de:bsz:180-madoc-393444
Keywords: H25; M13; O31; O38; 330; R&D; subsidies; NTBFs; policy evaluation; treatment effects; patents